Strengthening Students' Religious Character Through the Use of Social Media YouTube Religious Content, Student Islamic Boarding Schools and Al-Qur'an Memorization (Research at STIT At-Taqwa Ciparay with STAI Yamisa Soreang Bandung) - Euis Komala; Tedi Priatna; Bambang Samsul Arifin; Mohammad Erihadiana (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study is motivated by the challenges of strengthening students' religious character in the digital era, including social media influences, materialistic lifestyles, and the lack of integration between formal education and Islamic values. It aims to identify and describe the objectives, programs, implementation processes, supporting and inhibiting factors, evaluation, and impacts of strengthening students' religious character through YouTube-based Islamic content, pesantren student programs, and Qur'an memorization (tahfidz) at STIT At-Taqwa Ciparay and STAI Yamisa Soreang. This research employs a qualitative comparative case study approach. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using an inductive process involving data reduction, data display, and conclusion drawing. The findings show that the programs aim to produce students who are faithful, pious, morally grounded, and resilient in the digital era. Implementation is carried out through digital Islamic literacy via YouTube, structured pesantren activities (such as congregational worship, classical Islamic studies, muhadharah, and moral training), and Qur'an memorization programs (tahsin and tahfidz). These processes are strengthened through habituation, reflection, and internalization of Islamic values. The study also identifies supporting factors, such as institutional leadership, educator competence, and student engagement, while challenges include technological limitations, diverse student backgrounds, and issues with content supervision. Overall, the programs contribute to improved discipline, empathy, patience, and the application of Islamic values in academic and social life, and produce an integrative model for strengthening students' religious character that combines digital media, pesantren-based education, and Qur'anic learning.